Characterization and cytotoxicity evaluation of Ixora coccinea-derived iron oxide microparticles for biomedical applications - Bharathy, Pavithra; Jayaprakash, Silpa; Allen Christopher M; Rajini prem G; Punniyakoti Veeraveedu Thanikachalam (Creative Pharma Assent, 2025)
Background: This study aimed to synthesise and characterise iron oxide microparticles (IOMPs) using Ixora coccinea flower extracts and evaluate their antioxidant, anti-inflammatory, cytotoxic, and antidiabetic activities. Methodology: IOMPs were synthesised using Ixora coccinea flower extract and characterised using XRD, UV-Vis, EDAX APEX, and SEM. Bioactivity evaluations included anti-inflammatory and antioxidant activities via egg albumin, BSA, and DPPH assays; cytotoxicity through Brine Shrimp Lethality and zebrafish embryonic toxicity assays at 5, 10, 20, 40, and 80 μg/ml; and antidiabetic activity via alpha-amylase and alpha-glucosidase inhibition. Results: Fe₂O₃MPs demonstrated potent anti-inflammatory (83% protein denaturation inhibition at 50 μg/ml), antioxidant (94.26% inhibition at 50 μg/ml), and antidiabetic (86% α-amylase and 84% α-glucosidase inhibition at 50 μg/ml) properties, surpassing diclofenac sodium and ascorbic acid. Cytotoxicity tests revealed low toxicity, with LC50 values of 80.5 μg/ml (Brine Shrimp) and 82.4 μg/ml (zebrafish). Discussion: This study presents an eco-friendly synthesis of Fe₂O₃ microparticles using Ixora coccinea extract as a reducing and stabilising agent. These microparticles hold promise for biomedical applications, including drug delivery, MRI contrast enhancement, and hyperthermia treatment. Further research must optimise the synthesis process and assess the in vivo biocompatibility and therapeutic efficacy. Conclusion: This study addresses the need for eco-friendly nanoparticles. Conventional iron oxide microparticle synthesis uses toxic chemicals, but Ixora coccinea flower extract offers a sustainable alternative. Evaluating Fe₂O₃MPs' cytotoxicity and bioactivity provides insights into biomedical applications, supporting future investigations that link nanotechnology and therapeutics.